2009
DOI: 10.1007/s12562-009-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of domoic acid in a bivalve Spondylus versicolor in association with that in plankton samples in Nha Phu Bay, Khanh Hoa, Vietnam

Abstract: Previously we reported that a significant level of domoic acid, a causative toxin for amnesic shellfish poisoning, was detected in bivalves belonging to a genus Spondylus from various tropical Asian countries. These findings indicate that causative plankton species for domoic acid widely distribute in these areas. In the present study, we monitored seasonal change of domoic acid level of Spondylus versicolor in association with that of plankton samples in Nha Phu Bay, Khanh Hoa, Vietnam from December 2004 to O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
1
14
1
2
Order By: Relevance
“…Total DA content in both sizes of plankton at 0.5 m from the sea surface was still very low (12.13-115.47 ng/l) compared to Vale and Sampayo, who recorded maximum DA levels in phytoplankton samples greater than 700 ng/l 35 . However, DA content from the fraction larger than 20 µm (12 ng/l) of this study was higher than in Nha Phu Bay, Vietnam 28 . Yotying found that total DA content in phytoplankton at Kham Yai island, Chonburi province, ranged between 0.49 and 2.04 ng/l 29 , which was low compared to our results.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Total DA content in both sizes of plankton at 0.5 m from the sea surface was still very low (12.13-115.47 ng/l) compared to Vale and Sampayo, who recorded maximum DA levels in phytoplankton samples greater than 700 ng/l 35 . However, DA content from the fraction larger than 20 µm (12 ng/l) of this study was higher than in Nha Phu Bay, Vietnam 28 . Yotying found that total DA content in phytoplankton at Kham Yai island, Chonburi province, ranged between 0.49 and 2.04 ng/l 29 , which was low compared to our results.…”
Section: Discussioncontrasting
confidence: 78%
“…Most previous DA studies focused on phytoplankton larger than 20 µm 9, 28 . Dao et al sug-gested that the width of the Pseudo-nitzschia cell was narrow enough to pass through a 20 µm mesh plankton net 28 . Yotying reported that DA can be detected in phytoplankton both larger and smaller than 20 µm 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…blooms: 30.0 gg −1 for C. gigas (Trainer et al, 2007) and 790 gg −1 for M. edulis (Bates et al, 1989). In addition, comparable to higher DA concentrations have been found in whole tissues of slow-depurating bivalves, such as the oyster Spondylus versicolor [(147 gg −1 (Dao et al, 2009)], the clam S. patula [308 gg −1 (Trainer et al, 2000)] and the scallop P. maximus [1569 gg −1 (Campbell et al, 2001)]. High DA concentrations in natural bivalve populations (up to 70 gg −1 ) usually occur during massive blooms of highly toxic Pseudo-nitzschia spp.…”
Section: Inter-specific Differences In Da Uptake and Eliminationmentioning
confidence: 83%
“…Significant levels of DA (145 mg DA g À1 whole tissue) have been detected in the spiny oyster (Spondylus), collected from the Philippines and Vietnam (Dao et al, 2009). However, the responsible species of Pseudo-nitzschia have not yet been identified.…”
Section: Asiamentioning
confidence: 99%